Rediscovering urban neighbourhoods - Residential Mobility Motivations of Urban Dwellers in Settlements of the 1950s - 1960s. - Stieß, Immanuel; Deffner, Jutta (My University, 2007)
In many European cities, post-war settlements of the 1950´s to the early 1970´s form a large part of the urban housing stock. Today, buildings as well as technical and social infrastructures are reaching the end of a maintenance cycle. Many housing estates no longer match contemporary housing needs and have been losing attractiveness to important groups of residents. In our contribution, life cycle management of urban neighbourhoods of the 1950´s-1970 s is suggested as an innovative approach to design transition strategies for urban neigbourhoods, taking the complex interplay of life cycles of buildings and infrastructures with those of urban residents into account. Drawing on a qualitative empirical survey on housing mobility decisions of intra urban and suburb to city movers in two German cities (Kiel and Goettingen), a target group model is presented. The model is taking the motivations and attitudes, the search criteria and the rationale of the mobility decision towards post-war housing estates into account. difu
Keywords: Nachbarschaft; Bewohner; Wohnumfeld; Wohnstandort; Wohnwunsch; Umzug; Bevölkerungswanderung; Wohnsiedlung; Wohngebiet; Mobilität; Erhebung; Sozialinfrastruktur; Infrastruktur; Wohnungswesen; Nachhaltige Entwicklung; Fallbeispiel; Motivation